Interlaboratory Comparison of Measuring Results of Magnetic Field near 400 kV Overhead Power Line - Grbić, Maja; Pavlović, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
The paper presents a comparison of measured results of magnetic field near 400 kV overhead power lines obtained by three laboratories. This interlaboratory comparison was performed to ensure confidence in the quality of the test results. The measured results were analysed with standard methods, using Еn number, based on which the evaluation of the laboratories was performed.
Keywords: measuring; interlaboratory comparison; non-ionizing radiation; magnetic field